Population pharmacokinetic and concentration--QTc models for moxifloxacin: pooled analysis of 20 thorough QT studies - Florian, Jeffry A; Tornøe, Christoffer W; Brundage, Richard; Parekh, Ameeta; Garnett, Christine E (Journal of clinical pharmacology, 2011)
To increase our understanding of important subject characteristics and design variables affecting the performance of oral moxifloxacin in thorough QT studies, population pharmacokinetic and concentration-QTc models were developed by pooling data from 20 studies. A 1-compartment model with first-order elimination described the pharmacokinetics. Absorption delay was modeled using 8 transit compartments. Mean (95% confidence interval) values for oral clearance, apparent volume of distribution, the first-order absorption rate constant, and mean transit time were 11.7 (11.5-11.9) L/h, 147 (144-150) L, 1.9 (1.7-2.1) 1/h, and 0.3 (0.28-0.34) hours, respectively. Overencapsulating the moxifloxacin tablet increased mean transit time by 138% and delayed time to maximum concentration by 0.5 hours but had a minimal effect on overall exposure. Administration with food decreased absorption rate constant by 27%. Women had higher moxifloxacin exposure compared with men, which was explained by lower body weights. A linear model described the concentration-QTc relationship with a mean slope of 3.1 (2.8-3.3) milliseconds per µg/mL moxifloxacin. Mean slopes for individual studies ranged from 1.6 to 4.8 milliseconds per µg/mL. Hysteresis between moxifloxacin plasma concentrations and QTc was modest, and incorporating this delay did not result in a different slope (3.3 milliseconds per µg/mL). There were no differences in slope estimates between men and women or among race categories.